The variable light environment within complex 3D canopies - Burgess, Alexandra Jacquelyn (2017)
With an expanding population and uncertain consequences of climate change, the need to both stabilise and increase crop yields is important. The relationship between biomass production and radiation interception suggests one target for improvement. Under optimal growing conditions, biomass production is determined by the amount of light intercepted and the efficiency with which this is converted into dry matter. The amount of light at a given photosynthetic surface is dependent upon solar movement, weather patterns and the structure of the plant, amongst others. Optimising canopy structure provides a method by which we can improve and optimise both radiation interception and also the distribution of light among canopy layers that contribute to net photosynthesis. This requires knowledge of how canopy structure determines light distribution and therefore photosynthetic capacity of a given crop species.